2009
DOI: 10.1093/cvr/cvp039
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ATP-sensitive K+ channels by caveolin-enriched microdomains in cardiac myocytes

Abstract: We demonstrate that K(ATP) channels are localized to caveolin-enriched microdomains. This microdomain association is essential for adenosine receptor-mediated regulation of K(ATP) channels in cardiac myocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 34 publications
3
36
0
1
Order By: Relevance
“…In vascular smooth muscle, caveolin-1 was described to interact with the K ATP channel and that this suppresses gating by reducing the sensitivity of channels to the stimulatory influence of MgADP (162). Kir6.2 was also described to associate with caveolin-3 (but not caveolin-1), and it was found that ventricular K ATP channels are negatively regulated by caveolin (256). A possible role for this interaction and the presence of K ATP channels in caveolae is to localize receptor signaling to K ATP channels in smooth muscle and the endothelium (606,687,688).…”
Section: Other Interacting Proteinsmentioning
confidence: 99%
“…In vascular smooth muscle, caveolin-1 was described to interact with the K ATP channel and that this suppresses gating by reducing the sensitivity of channels to the stimulatory influence of MgADP (162). Kir6.2 was also described to associate with caveolin-3 (but not caveolin-1), and it was found that ventricular K ATP channels are negatively regulated by caveolin (256). A possible role for this interaction and the presence of K ATP channels in caveolae is to localize receptor signaling to K ATP channels in smooth muscle and the endothelium (606,687,688).…”
Section: Other Interacting Proteinsmentioning
confidence: 99%
“…To test this scenario, mouse atrial myocytes were pretreated with M␤CD, which disrupts caveolae by depleting cholesterol (21,22). We confirmed that treatment with 3 mM M␤CD for 10 min did not affect I GIRK .…”
Section: Caveolar Disruption Abolishes Receptor Specificity Of Girkmentioning
confidence: 55%
“…Although the caveolae of ventricle modulate excitation-contraction coupling, ␤ 2 -adrenergic signaling, and ATP-sensitive K ϩ channel regulation (21,22,29), the role of caveolae in the atria remains unclear. The current data showed that caveolae can act as signaling platforms linking GIRK channels and GqPCRs in mouse atrial myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…20 Briefly, cells were pretreated with or without hypoxic preconditioning and then were spin down and resuspended in 0.5 M sodium carbonate (pH 11.0; 2 ml). Subsequently the cell homogenates were subjected to centrifugation at 4 C, and the supernatant was received.…”
Section: Purification Of Caveolin-enriched Membrane Fractionsmentioning
confidence: 99%
“…19 Immunoprecipitation experiments were performed according to the previous report. 20,21 The cardiac myocytes were isolated and then pretreated with or without hypoxic preconditioning prior to homogenization. The cells were lysed and centrifuged to get supernatant.…”
Section: Western Blot and Co-immunoprecipitationmentioning
confidence: 99%